(2x+3)/(3x-6) = (5x+3)/(5x - 9)

2 answers

cross multiply:
(2x+3)*(5x-9) = (3x-6)*(5x+3)

double distribution:
10x^2 - 3x -27 = 15x^2 - 21x - 18

combine like terms:

0 = 5x^2 -18x + 9

Then factor it to find two values of x
(2x+3)*(5x-9)=(3x-6)*(5x+3)

(2x+3)*(5x-9)=(5x+3)*(3x-6)

10x^2+15x-18x-27=15x^2+9x-30x-18

10x^2-3x-27=15x^2-21x-18

0=15x^2-10x^2+3x-21x+3x-18+27

5x^2-18x+9=0

If you want to know that solutions in google type:

quadratic equation online

When you see list of results click on:

webgraphingcom/quadraticequation_quadraticformula.jsp

When page be open in rectacangle type:

5x^2-18x+9=0

and click option solve it

You will see solution step-by-step